PRO DAN KONTRA UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS SEBAGAI LEX SPECIALIS ( Memaksimalkan Profesionalitas Pers dalam Menjalankan Aktifitas Jurnalistik ) - Saiful Amri; Putri Maulina; Al Zuhri (Universitas Teuku Umar, 2021)
The aims of this study is to examine how the pros and cons of Law Number 40 of 1999 concerning the Press as a lex specialis from a legal point of view. This research is a descriptive qualitative study with a literature review approach, which focuses on discussing the substance of the law and the issues under study in accordance with the relevant literature. The results of the study illustrate that there are pros and cons related to the position of the Law. No.40 of 1999 concerning the press as lex specialis. The pro side illustrates that press activities and various disputes that arise in it when referring to the press law that has been specially formulated is used to solve press problems specifically, so that it is considered a lex specialis. On the other hand, it emphasizes that the press law from various sides does not meet the requirements as a lex specialis because there is no clear legal basis for reference from any parent law.